A scoping review of the detection, epidemiology and control of Cyclospora cayetanensis with an emphasis on produce, water and soil. (28th January 2021) - Totton, S. C.; O'Connor, A. M.; Naganathan, T.; Martinez, B. A. F.; Vriezen, E. R.; Torrence, M. E.; Sargeant, J. M.
Abstract: Cyclospora cayetanensis is a parasite causing cyclosporiasis (an illness in humans). Produce (fruits, vegetables, herbs), water and soil contaminated with C. cayetanensis have been implicated in human infection. The objective was to conduct a scoping review of primary research in English on the detection, epidemiology and control of C. cayetanensis with an emphasis on produce, water and soil. MEDLINE® (Web of Science TM ), Agricola (ProQuest), CABI Global Health, and Food Science and Technology Abstracts (EBSCOhost) were searched from 1979 to February 2020. Of the 349 relevant primary research studies identified, there were 75 detection-method studies, 40 molecular characterisation studies, 38 studies of Cyclospora in the environment (33 prevalence studies, 10 studies of factors associated with environmental contamination), 246 human infection studies (212 prevalence/incidence studies, 32 outbreak studies, 60 studies of environmental factors associated with non-outbreak human infection) and eight control studies. There appears to be sufficient literature for a systematic review of prevalence and factors associated with human infection with C. cayetanensis . There is a dearth of publicly available detection-method studies in soil ( n = 0) and water ( n = 2), prevalence studies on soil ( n = 1) and studies of the control of Cyclospora (particularly on produce prior to retail ( n = 0)).